Development of AEI type germanoaluminophosphate (GeAPO-18) with ultra-weak acid sites and its catalytic properties for the methanol to olefin (MTO) reaction. Issue 20 (15th August 2017) - Ono, Kaito; Miyake, Koji; Nakai, Masahiro; Al Jabri, Hasna; Hirota, Yuichiro; Uchida, Yoshiaki; Tanaka, Shunsuke; Miyamoto, Manabu; Nishiyama, Norikazu
Abstract : Incorporating Ge into the aluminophosphate framework generated weakened Brønsted acid sites, leading to prolonged catalyst lifetimes in the MTO reaction. Abstract : Zeolites have been widely applied as sophisticated solid acid catalysts in chemical industries. Tuning the acidic properties of zeolites is very important to improve their catalytic performances and expand their utilization. Herein, we synthesized AEI-type Ge-incorporated aluminophosphate, GeAPO-18, by a dry gel conversion method in order to generate new acidity. GeAPO-18 had weaker Brønsted acid sites than the conventional SAPO-18. To confirm the effect of the substitution of Ge, we carried out the methanol to olefin (MTO) reaction over GeAPO-18 and the conventional SAPO-18. The catalyst lifetime of GeAPO-18 in the MTO reaction was longer than that over the conventional SAPO-18. The rate of coke deposition on GeAPO-18 was slower than that on the conventional SAPO-18. These results indicated that the decreased acid strength of GeAPO-18 could retard the coke formation via undesired successive reactions. The incorporation of Ge into the aluminophosphate zeolite framework was a crucial method for tuning the acid strength, which provides a new direction for the design of solid acid catalysts.